A conceptual analysis of Wasatiyyah (Islamic Moderation-IM) from Islamic Knowledge Management (IKM) perspective - Yaakub, Muhamadul Bakir; Othman, Khatijah (IIUM Press, International Islamic University Malaysia, 2017)
In the environment of globalization and information affluent, the issue of moderation represents the primary concerns of parents, educators, scholars, and leaders. Although the concept is somehow complicated and regarded as very much personal or religious in practices and thought. In fact, there is no definite answer to the question of how it takes place? In this direction, the purpose of the paper is to examines the Islamic Moderation (Wasatiyyah) background and analyse its common conceptual aspects or principles as an attempt to explore wider understanding of its specific or main conceptual aspects or principles from Islamic Knowledge Management (IKM) practices. This exploration is an initiative to critically reviewed, analysed and constructed the existing formulations of IM within contemporary understanding and practices. The focus was more toward identifying aspects of the relationship values of knowledge, its functions, and utilization within the practice of IM. From the essence of this study, IM was viewed as essential personality treats of an individual that determines an organizational productivity, and societal stability. In other words, the implications of this study covered various statuses of knowledge users that construct their Islamic Moderation Personality.